A Comparison of Three Extraction Methods for Phenolic Compounds and Antioxidant Activities from Moringa oleifera Leaves - Truong Kim Tai (Science Faculty of Chiang Mai University, 2019)
In our study, the proximate analysis of dried Moringa oleifera leaves was firstly evaluated; then three different extracts were obtained by using different extraction techniques including agitation (AG), sonication (SO) and aqueous (AQ) were used to investigate the phytochemical screening (total phenolic content (TPC) and total flavonoid content (TFC)) and antioxidant activities (2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay, 2,2¢-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) assay, ferric reducing ability of plasma (FRAP) assay and reducing power (RP) assay) of the Moringa leaves in order to find the best extraction method for further study. Finally, the presence of phenolic compounds was analyzed using high performance liquid chromatography (HPLC) analysis. The results showed Moringa leaves contained a large amount of carbohydrate and protein; while there was only small amount of lipid. The highest extraction yield was obtained aqueous method at 62.22 ± 0.68%. For phytochemical screening, the agitation presented the best results for highest total phenolic content at 74.87 ± 0.19 mg Gallic acid equivalent (GAE)/g dry weight and highest total flavonoid content at 18.46 ± 0.25 mg Catechin equivalent (CE)/g dry weight, respectively. Besides, agitation method also showed significantly different in antioxidant abilities compared to the others. Due to dose-dependent manners of all extracts to scavenging DPPH and ABTS free radicals; it strongly reconfirmed the correlation of TPC to antioxidant abilities. Thus, finding the most effective extraction method for highest yield and phenolic compound content is beneficial for achieving greater antioxidant ability and can be applied in further works in the food and pharmaceutical industry.